Pornography beyond the media - Luiz A. Calmon Nabuco Lastória (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
The aim of this article is to reflect on pornography in consumer society nowadays. The link between pornographic literature and the French Revolution will be our starting point. We will continue then to show how liberal consumer societies represent a particular synthesis of freedom and pleasure.